PBP4 activity and its overexpression are necessary for PBP4-mediated high-level β-lactam resistance - Basuino, Li (J Antimicrob Chemother, 2018)
BACKGROUND: PBP4 is typically considered unimportant for conferring high-level β-lactam resistance in Staphylococcus aureus. Mutations in PBP4 have been associated with β-lactam non-susceptibility among natural strains of S. aureus. We have previously shown that PBP4 can mediate high-level β-lactam resistance in laboratory-generated strains passaged in β-lactam antibiotics. Mutations in the pbp4 promoter that up-regulate its expression and missense mutations that surround PBP4’s active site were detected in high frequencies among passaged strains, suggesting PBP4 plays a key role in resistance. How these mutations participate in PBP4’s ability to provide high-level β-lactam resistance is unknown. OBJECTIVES: To determine whether enzymatic activity of PBP4 is required for high-level β-lactam resistance and to investigate how the pbp4-associated mutations provide β-lactam resistance. METHODS: The catalytic activity of PBP4 was disabled through introduction of a serine to alanine point mutation in its active site (Ser-75→Ala) in a representative and well-studied passaged strain, CRB. pbp4 promoter and missense mutations detected in CRB were reconstituted in a WT strain individually and in combination. β-Lactam resistance of the resultant strains was evaluated by population analysis. Bacterial peptidoglycan composition of the pbp4 mutants was evaluated with and without antibiotic treatment using LC. RESULTS: PBP4 inactivation imparted complete β-lactam susceptibility of CRB. Reconstitution of PBP4 missense mutations alone did not impart β-lactam resistance, but did so in synergism with pbp4 promoter mutation. A similar synergistic interaction of pbp4 mutations was observed in enhanced peptidoglycan cross-linking upon antibiotic treatment. CONCLUSIONS: PBP4’s activity and overexpression both contribute to high-level β-lactam resistance.